A Revolução De 1930 E O Processo De Centralização Política Na Bahia-Brasil (1930-1933) (Global Journal of Human-Social Science, 2021)
This paper analyzes the process of centralization of power that took place in Brazil after the victory of the revolutionary movement that ocurred 1930. It discusses the role played by Bahia along with the so called Bloco do Norte, wich was the foundation of the new regime, especially in the early years of Getúlio Vargas' provisional and discretionary government that lasted from 1930 to 1934.
Keywords: revolution of 1930; provisional government; political centralization; bahia